EFEKTIVITAS MEDIA PEMBELAJARAN E-LEARNING TERHADAP PRESTASI BELAJAR MATA PELAJARAN FIQIH DI MTS AL FATAH JABON SIDOARJO - Ika Nur Rokhmawati; Rosichin Mansur; Zuhkriyan Zuhkriyan (VICRATINA, 2020)
The development of information technology offers a concept of teaching and learning based on information technology. This concept is  known as e-learning which brings the influence of conventional learning into digital form. The concept of e-learning has been widely used by the community such as the growing effectiveness of e-learning  in educational institutions. By applying the e-learning learning strategy, the researchertried  to examine the effectiveness of the use of e-learning  media on the achievement of fiqh learning in MTs Al Fatah JabonSidoarjo. The research was conducted at MTs Al Fatah JabonSidoarjo. The research was a descriptive qualitative study with observation, interview and documentation methods. Moreover, the researcher analyzed using data education, data presentation, and data conclusions. The results of this study indicate that the application of e-learning media in fiqh learning has not been stated to be effective in student achievement.